Phenol and Benzoate Metabolism by Pseudomonas putida: Regulation of Tangential Pathways - Feist, Carol F. (J Bacteriol, 1969)
Catechol occurs as an intermediate in the metabolism of both benzoate and phenol by strains of Pseudomonas putida. During growth at the expense of benzoate, catechol is cleaved ortho (1,2-oxygenase) and metabolized via the β-ketoadipate pathway; during growth at the expense of phenol or cresols, the catechol or substituted catechols formed are metabolized by a separate pathway following meta (2,3-oxygenase) cleavage of the aromatic ring of catechol. It is possible to explain the mutually exclusive occurrence of the meta and ortho pathway enzymes in phenol- and benzoate-grown cells of P. putida on the basis of differences in the mode of regulation of these two pathways. By use of both nonmetabolizable inducers and blocked mutants, gratuitous synthesis of some of the meta pathway enzymes was obtained. All four enzymes of the meta pathway are induced by the primary substrate, cresol or phenol, or its analogue. Three enzymes of the ortho pathway that catalyze the conversion of catechol to β-ketoadipate enol-lactone are induced by cis,cis-muconate, produced from catechol by 1,2-oxygenase-mediated cleavage. Observations on the differences in specificity of induction and function of the two pathways suggest that they are not really either tangential or redundant. The meta pathway serves as a general mechanism for catabolism of various alkyl derivatives of catechol derived from substituted phenolic compounds. The ortho pathway is more specific and serves primarily in the catabolism of precursors of catechol and catechol itself.